Mechanism of fault activation and water-conducting disasters induced by mining activities - Jian Chen; Lianchong Li; Wenqiang Mu; Xinrui Li (Geomatics, Natural Hazards & Risk)
Stress disturbances induced by mining activities are among the primary factors promoting deep fault activation. In coal seam mining under the threat of high-pressure confined water, fault activation significantly increases the risk of water inrush. This study employs theoretical analysis, numerical simulations, and field micro-seismic (MS) monitoring to investigate the fault activation-induced water-conducting processes in mining areas under deep confined water conditions. Theoretical and numerical analyses were conducted to identify the shortest water-conducting pathway triggered by fault activation. Field MS data revealed that fault activation under mining influence progresses through three distinct stages: the abutment stress propagation stage, the abutment stress disturbance stage, and the abutment stress action stage. By analyzing the characteristics of fault activation, this research provides a theoretical foundation for early warning and prevention of geological hazards induced by fault activation.